Pengembangan Modul Kimia Terintegrasi HOTS pada Materi Laju Reaksi di SMAN 1 Sungayang - Emmilya Martin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Most of the learning materials used by teachers are not integrated with higher order thinking skills (HOTS). This research aims to develop a Chemistry module Integrated with HOTS in Reaction Rate Materials that is valid and practical. This research is used the development research method (Research and Development) that included defining, designing, and developing stage. The data were collected by validity sheets and practicality questionnaire sheets. Validity sheets were completed by 2 chemistry lecturers and 1 chemistry teacher. Practicality questionnaire sheets were completed by 21 grade XI students in SMAN 1 Sungayang. Data were analyzed using descriptive quantitative method. The result of this research are: 1) the validity of the module is categorized as very valid (97,5%), 2) the practicality of the module is categorize as very practical (91,2%). The results of this study indicate that the chemistry module developed can be used as a learning materials for students. Keywords: module, HOTS, development